Medicines under additional monitoring in the European Union - Esther Salgueiro; Gloria Manso; Fernando Neira; Sandra Ortega; Luis H Martín Arias; Maria Sainz (Farmacia Hospitalaria)
Objective: The objective of this study was to analyse the characteristics of medicines subject to additional monitoring. We assessed the following aspects: the criteria applied to approve a medicine as being subject to additional monitoring; the authorized dispensing conditions; the pharmacological groups to which they belong; and their post-authorisation safety. Method: We analysed the list published by the European Medicines Agency in January 2017 (EMA/245297/2013 Rev.41). Information for the analysis was obtained from the web sites of the European Medicines Agency and the Spanish Agency of Medicines and Medical Devices. Results: We assessed 316 medicines subject to additional monitoring. The most common criterion used to assign a medicine as being subject to additional monitoring was it being a new active substance (n = 197 [62.3%]). Other common criteria were requiring a post-authorisation safety study (n = 52 [16.5%]) and being a biologic medicine but not a new active substance (n = 49 [15.5%]). Regarding dispensing conditions, nearly 66% of these medicines were authorized under restricted conditions. Until January 2017, the Spanish Agency of Medicines and Medical Device published 14 safety reports related to medicines subject to additional monitoring. Conclusions: The group of medicines subject to additional monitoring mainly includes new active substances. The most common pharmacological group is antineoplastic and immunomodulating agents. The postauthorisation safety study has already produced information published by the Spanish Agency of Medicines and Medical Devices.